2008
DOI: 10.1016/j.freeradbiomed.2007.12.016
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine enhances the lung cancer inhibitory effect of epigallocatechin-3-gallate and forms a new adduct

Abstract: The major tea polyphenol, (-)-epigallocatechin-3-gallate (EGCG), inhibits carcinogenesis in many in vivo models. Many potential mechanisms of action have been proposed based on cell line studies, including pro-oxidant activity. In the present study, we studied the effect of N-acetylcysteine (NAC) on the inhibitory effects of EGCG on lung cancer cell growth. We found that NAC (0 -2 mM) dosedependently enhanced the growth inhibitory activity of EGCG against murine and human lung cancer cells. The combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Previous reports indicated that oxidized EGCg reacts rapidly with a thiol group of cysteine residues in GSH or NAC to form thiol adducts, 19,25) but no EGCg-adducts were detected by HPLC analysis under this experimental condition with a 10-fold molar excess of thiol compounds (data not shown). GSH and NAC have been found to have an antioxidant role by direct scavenging of reactive oxygen species such as hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Previous reports indicated that oxidized EGCg reacts rapidly with a thiol group of cysteine residues in GSH or NAC to form thiol adducts, 19,25) but no EGCg-adducts were detected by HPLC analysis under this experimental condition with a 10-fold molar excess of thiol compounds (data not shown). GSH and NAC have been found to have an antioxidant role by direct scavenging of reactive oxygen species such as hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 48%
“…17) Recently, it was found that oxidation of polyphenols with a catechol structure in the B-ring leads to the formation of a polyphenol quinone, which reacts electrophilically with thiol groups in GSH or protein thiols to form covalent thiol-flavonoid adducts. 18,19) More recently, we found that 3,4-dihydroxyphenyl acetic acid and EGCg form covalent adducts with protein thiols (-actin and glyceraldehyde-3-phosphate dehydrogenase: GAPDH respectively) via autoxidation (Fig. 2.).…”
mentioning
confidence: 93%
“…A number of possible non-covalent and covalent binding modes for EGCG to misfolded polypeptides have been postulated: non-site specific interaction with exposed hydrophobic surfaces through the hydrophobic effect (Ehrnhoefer et al 2008), site-specific hydrogen bonding (H-bonding) (Maiti et al 2006), aromatic π-π-stacking (Scheraga et al 1962), site-specific covalent binding, such as formation of disulfidebridges via cysteines (Lambert et al 2008) and formation of Schiff bases via primary amines (Ishii et al 2011). EGCG binding to amyloidogenic polypeptides has been analyzed using various biophysical and biochemical methods.…”
Section: 4 Towards a Holistic Molecular Mechanism For Egcg-amyloid mentioning
confidence: 99%
“…A number of possible non-covalent and covalent binding modes for EGCG to misfolded polypeptides have been postulated: non-site specific interaction with exposed hydrophobic surfaces through the hydrophobic effect , site-specific hydrogen bonding (H-bonding) (Maiti et al 2006), aromatic --stacking (Scheraga et al 1962), site-specific covalent binding, such as formation of disulfidebridges via cysteines (Lambert et al 2008) and formation of Schiff bases via primary amines (Ishii et al 2011). EGCG binding to amyloidogenic polypeptides has been analyzed using various biophysical and biochemical methods.…”
Section: The Effect Of ( )-Epigallo-catechin-(3)-gallate On Amyloidogmentioning
confidence: 99%